1995
DOI: 10.1002/srin.199501121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfur on the stability of cementite

Abstract: Cementite FesC is an unstable carbide, which should decompose to iron and graphite. It was possible to grow cementite on iron samples in flowing CO-H 2-H20-H2S mixtures at temperatures between 400-700 "C, The cementite is stabilized by adsorbed sulfur, preventing graphite deposition, which would initiate metal dusting. Thus, this corrosion phenomenon, occurring in CO-H 2-H20 and other strongly carburizing atmospheres can be suppressed by the presence of some H 2S. The range of H 2S/H 2 ratios and temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 26 publications
(4 reference statements)
3
38
1
Order By: Relevance
“…8) Sulphur adsorption on metallic iron is very strong, which effectively retards the carburisation process. Grabke et al 1,2) reported that the iron carburisation reaction rate began to decrease at sulphur activities a s Ͼ10 Ϫ4 , or at P H 2 S /P H 2 Ͼ10…”
Section: Effect Of Sulphur On Cementite Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…8) Sulphur adsorption on metallic iron is very strong, which effectively retards the carburisation process. Grabke et al 1,2) reported that the iron carburisation reaction rate began to decrease at sulphur activities a s Ͼ10 Ϫ4 , or at P H 2 S /P H 2 Ͼ10…”
Section: Effect Of Sulphur On Cementite Formationmentioning
confidence: 99%
“…The fraction of iron surface covered by sulphur can be calculated using data reported by Grabke et al 1) Calculated results are shown in Fig. 4.…”
Section: Effect Of Sulphur On Cementite Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since iron carbide is metastable at all temperatures compared with graphite and its saturated solution in iron, it is easy to decompose to solid carbon and metallic iron at elevated temperature. [4][5][6][7][8] The first commercial scale process for producing iron carbides at the Trinidad island did not succeed. This process needs long residence times and a few residual iron oxides leaves in the iron carbide depending on ore type.…”
Section: Introductionmentioning
confidence: 99%
“…The yield and the stability of iron carbide have been paid more attention. In 1995, Grabke and Müller-Lorenz 9) found that sulfur has the effect on the stability of iron carbide. In 1997, Hayashi and Iguchi 4,5) reported the synthesis of iron carbide by reaction of iron ores with H 2 -CO gas mixtures bearing traces of sulfur.…”
Section: Introductionmentioning
confidence: 99%